ProAKAP4 concentration in fresh canine semen and its correlation with motility parameters - Djemil Bencharif; Rédha Belala; Nora Mimoune; Dolorès Le Couazer; Hamed Farnia (Veterinary and Animal Science)
This study aimed to evaluate proAKAP4concentrations in canine fresh semen and to determine their correlation with sperm motility and fertility parameters. For this purpose, 26 ejaculates from 18 dogs were analyzed. Motility and kinetic parameters of the sperm-rich fractions were assessed by a computer assisted semen analyzer (Hamilton Thorne HT-IVOS II, USA). ProAKAP4 concentrations were measured (containing either the spermatic, urethral, or prostatic fraction) using the Dog 4MID® kit (4BioDx, France). In the spermatic fractions, on average, the proAKAP4 concentration was 17.08 ng/106spermatozoid (spz) with a total motility of 75.92 % and progressive motility of 58.08 %. Spearman test showed a positive correlation between proAKAP4 concentrations and the total motility (r = 0.584; p = 0.08), progressive motility (r = 0.6336; p = 0.0005), and the velocity parameters: VAP (r = 0.4178; p = 0.0337), VSL (r = 0.3919; p = 0.0477) and mainly VCL (r = 0.5266; p = 0.0057). For fertility monitoring, 5 ejaculates were used to perform artificial insemination (AI). The mean proAKAP4 concentration was 25.91 ng/106spz with an average total motility of 74.4 % and progressive motility of 53 %. Four female dogs were pregnant with litter sizes ranging from 4 to 11 puppies. To conclude, this is the first study presenting the significant correlation between proAKAP4 concentration and sperm motility parameters in dogs. Further investigations with a large number of animals are recommended to test the correlation between proAKAP4 and fertility parameters.